Impact of ambient temperature on inflammation-induced encephalopathy in endotoxemic mice: role of phosphoinositide 3-kinase gamma - Lang, Guang-Ping; Ndongson-Dongmo, Bernadin; Lajqi, Trim; Brodhun, Michael; Han, Yingying; Wetzker, Reinhard; Frasch, Martin G.; Bauer, Reinhard (Journal of neuroinflammation, 2020)
Sepsis-associated encephalopathy (SAE) is an early and frequent event of infection-induced systemic inflammatory response syndrome. Phosphoinositide 3-kinase γ (PI3Kγ) is linked to neuroinflammation and inflammation-related microglial activity. In homeotherms, variations in ambient temperature (Ta) outside the thermoneutral zone lead to thermoregulatory responses, mainly driven by a gradually increasing sympathetic activity, and may affect disease severity. We hypothesized that thermoregulatory response to hypothermia (reduced Ta) aggravates SAE in PI3Kγ-dependent manner.
Gesehen am 12.11.2020